Star trek: the next generation: terra incognita ebook Terra incognita. - Tipton, David (Star Trek: The Next Generation: Terra Incognita (2018)., 2019)
Following their clash with their villainous doubles from the Mirror Universe, the Enterprise crew returns to business as usual, little realizing the serpent in their midst–one of their own has been replaced! Six stories focusing on fan-favorite crew members of the Enterprise-D–including Deanna Troi, Wesley Crusher, and Selar–each connected by the machinations of this sinister doppelgänger. What does Mirror Barclay want, and what's to become of his Prime-universe counterpart? Author: Scott Tipton, David Tipton. Illustrator: Tony Shasteen, Angel Hernandez, Carlos Nieto. ® AND © 2019 CBS STUDIOS INC. STAR TREK AND RELATED MARKS ARE TRADEMARKS OF CBS STUDIOS INC. ALL RIGHTS RESERVED.